The Derriford twelve commandments of emergency medicine: a model for good practice in a changing world, or a survival guide for new medical staff. Issue 12 (25th November 2008) - Smith, J E; Higginson, I; Guly, H R; Grant, I C; Belsham, P; Hicks, A; Alao, D; Boon, D
Abstract : Time is a precious commodity and with more junior doctors coming through our departments for shorter periods of time it has been useful to lay down some ground rules to facilitate their induction. These are presented in the form of the twelve commandments of emergency medicine.